Genetic transitions in the Neolithic and Bronze Age at Mas d’en Boixos (Catalonia, Spain) - Xavier Roca-Rada; Daniel R. Cuesta-Aguirre; Diana C. Vinueza-Espinosa; Roberta Davidson; Shyamsundar Ravishankar; Leonard Taufik; Núria Armentano; Xavier Esteve; Yassine Souilmi; João C. Teixeira; Assumpció Malgosa; Bastien Llamas; et al. (iScience)
Summary: Mas d’en Boixos is a key prehistoric site in Northeastern Iberia spanning from the Early Neolithic to the Late Iron Age. We analyzed genome-wide data from eight individuals and ten mitogenomes, dated to the Middle Neolithic and Early Bronze Age, alongside three previously published Iron Age individuals. Two Middle Neolithic individuals buried together were first-degree maternal relatives and carried Western Hunter-Gatherer, Anatolian, and residual Magdalenian-associated ancestries. Conversely, six Early Bronze Age individuals buried in a hypogeum exhibited distinct mitochondrial lineages. Among them, three were third-degree relatives, and all males shared a Y-chromosome lineage, consistent with a collective burial of an extended family within a patrilocal society practicing possible female exogamy. These individuals showed genetic continuity with additional Steppe-related ancestry, which displayed a subtle southward gradient across Iberia. We also identified an Eastern European mitochondrial lineage—challenging the proposed male-driven Bronze Age transition—and Mediterranean gene flow—suggesting dynamic interactions across the sea.